PENGARUH PAJAK BUMI BANGUNAN PEDESAAN PERKOTAAN DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA PROVINSI SULAWESI TENGAH - Syunandar B, Andi (Katalogis, 2017)
Purpose of this study are : 1) to determine and anlyze simultaneous influence of rural-urban property taxes and land acquisition fess to capital expenditure in district/ towns in Central Sulawesi Province; 2) to determine and anlyze partial influence of rural-urban property taxes on capital expenditure in district/ towns in Central Sulawesi Provinc; 3) to determine and analyze partial influence of land acquisition fees on capital expenditure in district/ towns in Central Sulawesi Province. The study applies verificative approach and select 11 district/ towns inCestral Sulawesi Provinceas it samples. Mtehods of data collection applied are: interviews, observations, and documents. Data is analyze with multiple linear regressions. The results show that: 1) rural-urban property taxes and land acquisition fees have silmutanoeus influences on capital expenditures in district/ towns in Central Sulawesi Provinces; 2) rural-urban property taxes partially have significant on capital expenditures in district/ town in Central Sulawsi Province; 3)land acquisition fees partially have significant influence on capital expenditures in district/ towns in Central Sulawesi Province.